Penyuluhan Kesiapsiagaan Bencana Pandemi Covid 19 di Desa Harapan Kabupaten Bengkulu Tengah - Agus, Nour Farozi; Sosinarti, Sosinarti; Julita, Julita; nabila, Tiara; Febriansyah, Ridho ravi (Jurnal Kewirausahaan dan Bisnis, 2021)
Health issues are one of the important things to consider for the survival of each individual. The world is now faced with the emergence of a new virus that spreads rapidly and greatly disrupts the continuity of life globally. At the end of 2019, a new virus was found in China, precisely in Wuhan Province. In 2020, WHO declared Covid-19 (Coronavirus Deseases 2019) as a pandemic so that new regulations were created to prevent the spread of this virus because it is transmitted from human to human. The incidence of Covid-19 continues to increase. It is necessary to increase 5M preparedness to break the transmission of Covid-19. Several studies have revealed that health education with audiovisual educational media is effective in improving community preparedness during the Covid-19 pandemic.